General health and its relation to the quality of life and alcohol consumption in a Polish cohort of medical students – preliminary results of POLLEK survey - Barański, Kamil; Szemik, Szymon; Kaleta-Pilarska, Angelina; Kowalska, Małgorzata (Frontiers in Public Health, 2023)
Introduction First-year students of medicine are at higher risk of stress related to the new environment and study overload. Such factors can play a role and have an impact on their quality of life and general health status which can cause possible problems with alcohol use. The aim of the study is to assess the relationship between mentioned factors in the Polish cohort of first-year medical students. Materials and methods The quality of life has been assessed within the WHOQOL-BREF questionnaire, the general health status was assessed via GHQ28, and alcohol consumption was assessed the by AUDIT questionnaire. Due to the lack of signature informed consent and lack of data, 381 (72%) students out of 525 were included in the final analysis. Result The majority of the 1-year students were females 68%; (n = 259) vs. 32% (n = 122) males. Half of the students had lowered risk of distress. However, females had a higher risk of having higher scores in GHQ-28 than males. In relation to the assessment of the quality of life, the students with a lower level of distress (<32 points in GHQ-28) had better results in each WHOQOL domain. There was no association between general health status and alcohol use. For the students who had possible problems with alcohol use the OR was 1.15 95% CI (0.73–1.80) and for students who were probably addicted OR was 1.07 95% CI (0.33–3.41). Conclusion The total quality of life in first-year Polish medical students is relatively high; however, half of them suffer because of distress and around 30% have some alcohol problems. Females are more likely to have higher GHQ-28 scores than males.